A Review on the Synthesis of Chitosan From Different Waterbodies Exoskeleton Species and Its Application in Treating Water/Wastewater - Achsan, Kanzul Fikri (Progress in Engineering Application and Technology, 2021)
Chitin is the second most abundant biopolymers in the world after cellulose. It can be found in exoskeleton, mollusk, fungi, and many others. Chitosan is the main derivatives of chitin. In this paper, a review on the synthesis of chitosan from different exoskeleton species, its characterization and application treating water/wastewater is discussed. The extraction of chitosan can be done by going through demineralization, deproteinization, and deacetylation process, with decolorization as the optional stage. The characterization of chitosan by Fourier Transform Infrared Spectroscopy (FTIR) was shown in this paper. From the FTIR spectra, several functional group of chitosan can be seen, like NH2, amide group, C-O. The application of chitosan on treating water/wastewater was reviewed. Chitosan is used as bio-absorbent in treating the water/wastewater. From the data obtained, the use of chitosan can reduce significance value of constituents, and metals. The use of chitosan can reduce the turbidity of water/wastewater.